Humanized single domain antibodies neutralize SARS-CoV-2 by targeting the spike receptor binding domain (2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spreads worldwide and leads to an unprecedented medical burden and lives lost. Neutralizing antibodies provide efficient blockade for viral infection and are a promising category of biological therapies. Here, using SARS-CoV-2 spike receptor-binding domain (RBD) as a bait, we generate a panel of humanized single domain antibodies (sdAbs) from a synthetic library. These sdAbs reveal binding kinetics with the equilibrium dissociation constant (KD) of 0.99–35.5 nM. The monomeric sdAbs show half maximal neutralization concentration (EC50) of 0.0009–0.07 µg/mL and 0.13–0.51 µg/mL against SARS-CoV-2 pseudotypes, and authentic SARS-CoV-2, respectively. Competitive ligand-binding experiments suggest that the sdAbs either completely block or significantly inhibit the association between SARS-CoV-2 RBD and viral entry receptor ACE2. Fusion of the human IgG1 Fc to sdAbs improve their neutralization activity by up to ten times. These results support neutralizing sdAbs as a potential alternative for antiviral therapies.